Scorpion safety products PC diagnosing and fixing system - Muchingami, Carrington (Midlands State University, 2019)
The purpose of this research was to come up with a solution for problems that were identified at Scorpion Safety Products. The main objectives of the system are to ensure that computer users at Scorpion Safety Products are equipped with the knowledge to fix problem they encounter on a day to day basis in the workplace. Users in various departments depended on an external subcontractor for every little problem faced and this resulted in the company having to fork over huge amounts of money for the upkeep of their computers. For this system, all users have to login to access this information and a log is created whenever user logs in so as to increase accountability of access. Data gathering methodologies such as interviews, questionnaires and observations where used so as to identify problems that were being faced by the staff at Scorpion Safety Products. For the development of a system to fix these problems, the developer used development tools such as Android Studio, Xampp, Adobe Photoshop and many others. As for further developments of the system, the developer will add a communication panel where user can interact with the admin.